ANALISIS KEPUASAN MASYARAKAT TERHADAP PROGRAM INOVASI LAPAK LAYANAN CEPAT ADMINISTRASI - sintia, Ana; Puspitarini, Renny; Rahmadi, Andhi Nur (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2024)
This research was conducted in Sekarkare Village, Dringu District, Probolinggo Regency, with the aim of finding out community satisfaction with the innovation of the Village Administration Quick Service Stall (LAPAK) program in Sekarkare Village. This research uses a quantitative approach involving 180 respondents during the 2023 period. The data used comes from primary and secondary sources collected through questionnaires and analysis using the spreadsheet data analysis method. The results of the research show that the Community Satisfaction Index (IKM) is measured based on 9 indicators with the guidelines of Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 14 of 2017. The IKM Conversion Value is calculated using the Weighted NRR x 25 formula, resulting in an IKM conversion value of 82.53 which is categorized as service quality "B" or "Good/Satisfied". Community satisfaction with the innovation of the LAPAK program in Sekarkare Village received the highest index scores for two elements, namely the first and sixth elements, each of which had a score of 417 with a conversion of 84.1 and category "B" or "Satisfied". Meanwhile, the lowest score was 404.5 with a conversion of 81.6, which is still in the "B" or "Satisfied" category. Kata kunci: Public Services, Innovation, Administration, Evaluation, Community Satisfaction Survey